PERANCANGAN BUKU FOTOGRAFI DOKUMENTASI KEGIATAN KESENIAN DI KAMPUNG JELEKONG - Sherilyn Silviani; Sandy Rismantojo; R.A. Dita Saraswati (Serat Rupa: Journal of Design, 2019)
Jelekong Village is located in the south of Bandung and is a craft center for make-by-order painting artisans. The late Mr. Odin Rohidin started this artistic activity in the 1970s. Aside from paintings, Jelekong Village is also active in such activities as Pencak Silat, Wayang Golek, and the Jaipong dance. Unfortunately, this village has a hard time developing in terms of facilities and infrastructures, which is caused by lack of attention from the local government. This results in the fact that not many people, even those in Bandung know the whereabouts of the artisans in Jelekong Village, who in fact play an important role in preserving the traditional Sundanese arts and culture. That is why, there is a need to design a media that is able to document and narrate the things that these artisans do in Jelekong Village and their daily struggles in creating art without being acknowledged and appreciated by their own people. By designing a documentary photography book, it is expected that the people of Bandung will be more informed about these artisans and will support the making of better facilities and infrastructures to rise up their spirit in creating more arts.